HPLC determination of hemoglobins to establish reference values with the aid of statistics and informatics - Ondei, L. S. [UNESP]; Zamaro, P. J A [UNESP]; Mangonaro, P. H. [UNESP]; Valêncio, C. R. [UNESP]; Bonini-Domingos, C. R. [UNESP] (My University, 2007)
The purpose of the present study was to establish reference values for hemoglobins (Hb) using HPLC, in samples containing normal Hb (AA), sickle cell trait without alpha-thalassemia (AS), sickle cell trait with alpha-thalassemia (ASH), sickle cell anemia (SS), and Hb SC disease (SC). The blood samples were analyzed by electrophoresis, HPLC and molecular procedures. The Hb A2 mean was 4.30 ± 0.44% in AS, 4.18 ± 0.42% in ASH, 3.90 ± 1.14% in SS, and 4.39 ± 0.35% in SC. They were similar, but above the normal range. Between the AS and ASH groups, only the amount of Hb S was higher in the AS group. The Hb S mean in the AS group was 38.54 ± 3.01% and in the ASH it was 36.54 ± 3.76%. In the qualitative analysis, using FastMap, distinct groups were seen: AA and SS located at opposite extremes, AS and ASH with overlapping values and intermediate distribution, SC between heterozygotes and the SS group. Hb S was confirmed by allele-specific polymerase chain reaction. The Hb values established will be available for use as a reference for the Brazilian population, drawing attention to the increased levels of Hb A2, which should be considered with caution to prevent incorrect diagnoses. ©FUNPEC-RP.
Keywords: Hemoglobins; High-performance liquid chromatography; Reference values; hemoglobin; hemoglobin A; hemoglobin A2; hemoglobin C; hemoglobin F; hemoglobin S; alpha thalassemia; blood sampling; controlled study; electrophoresis; hemoglobin determination; high performance liquid chromatography; human; phenotype; reference value; sickle cell anemia; sickle cell trait; alpha-Thalassemia; Brazil; Chromatography, High Pressure Liquid; Computational Biology; Electrophoresis; Genetic Techniques; Heterozygote; Humans; Models, Statistical; Mutation; Phenotype; Reference Values; Sickle Cell Trait